PENGARUH STRUKTUR MODAL DAN PERPUTARAN MODAL KERJA TERHADAP PROFITABILITAS (STUDI PADA PERUSAHAAN PERBANKAN YANG TERDAFTAR DI BEI TAHUN 2015-2017) - Naning Adindah Putri; Ronny Malavia Mardani; Budi Wahono (E-JRM : Elektronik Jurnal Riset Manajemen, 2019)
ABSTRACTThe aim of this research is to find out the effects of Capital Structure and Working Capital Turnover toward the Profitability of Banking Companies. This research uses explanatory research. The sample selection technique used in this research is purposive sampling with some criteria and 25 Banking Companies listed in Indonesia Stock Exchange period 2015-2017 are selected. The techniques of data analysis used in this research are multiple linear regression analysis, normality test, classic assumption test consisting of multicollinearity test, heteroscedasticity test and autocorrelation test. This research also uses hypothesis testing which consists of f test and t test. The results of the research show that the Capital Structure has positive effects on the Profitability and Working Capital Turnover has positive effects on the profitability of the banking companies listed in Indonesia Stock Exchange in 2015-2017.Keywords: Capital Structure, Working Capital, Profitability